Data mining in personalized service of digital library - G, Nivedhitha; N, Rupavathy (International Journal of Engineering and Technology, 2018)
With the deepening of information engineering, people face increasing amounts of information resources and also the demand of information is more and more. The digital library is a wealth of information resources. Affording readers a richer layer of personalized service is a new objective for the growth of these digital libraries. The data mining techniques to elicit useful information from a bunch of clutter information, in parliamentary procedure to provide efficient technical support for personalized services of digital libraries. The feasibility of information mining technology in digital libraries is analyzed in this paper. It also discusses the information mining technology in the digital library applications and the feasibility analysis for the data mining applications in digital libraries.